Influência da fragmentação de habitats no fluxo gênico e estrutura cromossômica de espécies de anuros do bioma Mata Atlântica no sul do Brasil - Getelina, Manoela Alberton (2022)
The Atlantic Forest is a vast and heterogeneous forest biome, covering about 17% of Brazilian territory with only 12% of the original area remaining, resulting from an extremely fragmented landscape. Fragmentation can lead to population declines and isolation and thus cause chromosomal damage and affect genetic structure and variability. Among vertebrates, amphibians are the most threatened taxonomic group due to their physiological and biological characteristics such as skin permeability, low vagility, small body size, aquatic larval phase, among others. In this sense, this work aims to evaluate the impact of habitat fragmentation on genetic diversity and genomic instability in anurans populations in Atlantic Forest streams. The samplings were made in five fragments of different sizes, in three species (Crossodactylus schmidti, Boana curupi, and Vitreorana uranoscopa) restricted to stream environments in the Atlantic Forest biome. The initial hypothesis was that populations found in smaller forest fragments present larger genomic instability, accumulating more damage in the DNA of individuals, and a lower genetic variability, compared to populations in larger forest fragments. Our results show that even smaller fragments of up to 4.6 hectares can maintain specific amphibian habitat populations if present the necessary resources such as available water. Furthermore, populations in smaller fragments, even if they present more gnomic damage, in some cases possess considerable genetic diversity and can remain healthy with the preservation of the area. As for the larger fragments, such as Protected Units, in addition to maintaining a higher number of individuals due to the larger availability of resources, they also play an important role in the matrices where they are located, where they serve as the main spreaders of genetic variability to the other neighbor areas.